Evidence of improved power conversion efficiency in lead-free CsGeI3 based perovskite solar cell heterostructure via scaps simulation - Raj, Abhishek; Kumar, Manish; Bherwani, Hemant; Gupta, Ankit; Anshul, Avneesh (Journal of vacuum science and technology. B, Nanotechnology & microelectronics, 2021)
Simulation has been performed on fully lead-free inorganic cesium germanium tri-iodide (CsGeI3) perovskite solar cell heterostructure and achieved a champion power conversion efficiency (PCE) of ∼18.30% with significantly improved device parameters. The influence of thickness of an electron transport layer, a hole transport layer, an absorber, defect density, doping concentration, electron affinity, temperature, and series resistance issued for the optimization of the lead-free device is studied. It is confirmed via the scaps simulation results that this device is perfectly optimized with the experimental results and demonstrates the maximum possible improved power conversion efficiency in a fully inorganic lead-free CsGeI3 perovskite solar cell device. The final optimized device performance parameters are as follows: %PCE = 18.30%, %FF = 75.46%, Jsc = 23.31 mA/cm2, and Voc = 1.04 V. In the future, this efficiency may offer prominent potential as a substitute in a highly efficient green solar absorber material for photovoltaic applications after confirmation in the laboratory.